2022
DOI: 10.3390/nano12071040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Systemic Toxicity, Genotoxicity, and Early Phase Hepatocarcinogenicity of Iron (III)-Tannic Acid Nanoparticles in Rats

Abstract: Iron-tannic acid nanoparticles (Fe-TA NPs) presented MRI contrast enhancement in both liver cancer cells and preneoplastic rat livers, while also exhibiting an anti-proliferative effect via enhanced autophagic death of liver cancer cells. Hence, a toxicity assessment of Fe-TA NPs was carried out in the present study. Acute and systemic toxicity of intraperitoneal Fe-TA NPs administration was investigated via a single dose of 55 mg/kg body weight (bw). Doses were then repeated 10 times within a range of 0.22 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Taken together, the above results confirm that FT NPs can accumulate in the liver of rats with DEN-induced hepatocarcinogenicity, and 5 mg kg −1 is the optimum dose for MRI scanning. It should be noted that 5 mg kg −1 bw FT NPs is a safe dose based on our acute and subacute toxicity investigations, 20 which could be further considered as the initial dose in human studies. Regarding this DEN-induced rat model, repeated injection of a low dose of DEN was used to induce HCC in rats, which has been found to mimic human hepatocarcinogenesis and biologically and biochemically resemble human disease.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the above results confirm that FT NPs can accumulate in the liver of rats with DEN-induced hepatocarcinogenicity, and 5 mg kg −1 is the optimum dose for MRI scanning. It should be noted that 5 mg kg −1 bw FT NPs is a safe dose based on our acute and subacute toxicity investigations, 20 which could be further considered as the initial dose in human studies. Regarding this DEN-induced rat model, repeated injection of a low dose of DEN was used to induce HCC in rats, which has been found to mimic human hepatocarcinogenesis and biologically and biochemically resemble human disease.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Over decades, iron-based contrast agents have been extensively investigated because of their promise as an alternative to GBCAs . In our group, we have explored the potential of the ferric–tannic nanoparticles (FT NPs) to enhance the MRI signal in hepatic cell lines as well as in the liver of Wistar rats. , Interestingly, our previous study showed that FT NPs enhanced the MRI signal in pre-neoplastic lesions of diethylnitrosamine (DEN)-induced hepatocarcinogenicity in Wistar rats without inducing hepatotoxicity. , Moreover, the cellular uptake of FT NPs was found to be mediated by members of the solute carrier (SLC) family such as the organic anion transporter (OAT), which is reported to be highly expressed in eHCC . Therefore, it would be of great interest to explore the feasibility of FT NPs for early diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation